2021
DOI: 10.3390/metabo11060340
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Simvastatin on Lipidomic Markers of Cardiovascular Risk in Human Liver Cells Is Secondary to the Modulation of Intracellular Cholesterol

Abstract: Statins are the first-line lipid-lowering therapy for reducing cardiovascular disease (CVD) risk. A plasma lipid ratio of two phospholipids, PI(36:2) and PC(18:0_20:4), was previously identified to explain 58% of the relative CVD risk reduction associated with pravastatin, independent of a change in low-density lipoprotein-cholesterol. This ratio may be a potential biomarker for the treatment effect of statins; however, the underlying mechanisms linking this ratio to CVD risk remain unclear. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…noted increased conversion of linoleic acid to arachidonic acid in simvastatin treated THP-1 cells [37]. Similarly, statin treatment of cultured human hepatocytes (Hep3B) increased levels of lipids containing arachidonic acid (20:4) [38]. Although increased levels of omega-6 polyunsaturated fatty acids including linoleic acid are associated with reduced cardiovascular mortality [39], studies have shown a direct relationship between linoleic acid and elevated inflammatory markers in obesity [40].…”
Section: Significance Of Observed Differences In Specific Lipids and ...mentioning
confidence: 99%
“…noted increased conversion of linoleic acid to arachidonic acid in simvastatin treated THP-1 cells [37]. Similarly, statin treatment of cultured human hepatocytes (Hep3B) increased levels of lipids containing arachidonic acid (20:4) [38]. Although increased levels of omega-6 polyunsaturated fatty acids including linoleic acid are associated with reduced cardiovascular mortality [39], studies have shown a direct relationship between linoleic acid and elevated inflammatory markers in obesity [40].…”
Section: Significance Of Observed Differences In Specific Lipids and ...mentioning
confidence: 99%